Teachers’ Insight on the Urgency of Research in ELT on the Excellence of English Learning - Musahrain Musahrain; Nashruddin Nashruddin; Novalia Tanasy; Liqaa Habeb Al-Obaydi (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
To improve the quality of learning, teachers must have advanced knowledge of educational research. The purpose of this research is to investigate English teachers’ insights on the importance of research in English Language Teaching and its impact on the excellence of English language learning. The survey method with a quantitative approach and Focus Group Discussion were applied in this study. The population in this research were EFL teachers from junior high schools and senior high schools in South Sulawesi. The survey was conducted by sending online questionnaires to 50 English teachers randomly selected as research samples. Only those with 10 years or more teaching experience were included in the sample. The survey data were analyzed by using descriptive statistical technique. Furthermore, 5 of those 50 teachers with master (S2) qualification were involved in the FGD to gain in-depth understanding. The survey results indicate that most respondents (72,2%) understand the concept of educational research in ELT. In term of interest in research activities, 85% respondents show high interest. However, the level of involvement in research activities varies. The FGD results identify resource limitations and resistance to innovation as challenges in integrating scientific research. Evaluation with various modes is considered important to measure the effectiveness of integrating research findings in ELT into English language learning practices. Overall, the research-based learning approach is received positively among teachers. However, practical challenges need to be addressed to increase teacher engagement in research, and integrate educational research into teaching activities.